Structural‐based tunneling: preserving mutual anonymity for circular P2P networks. (11th August 2015) - Naghizadeh, A.; Berenjian, S.; Meamari, E.; Atani, R. Ebrahimi
Summary: Many methods are suggested to preserve anonymity of users for peer‐to‐peer (P2P) networks. Most of these methods, by relying on established anonymous solutions on client/server applications, are presented for unstructured P2P networks. However, structured overlays, by using distributed hash tables for their routing, do not resemble traditional paradigms. Therefore, current anonymous methods cannot be implemented for them easily. In this paper, we introduce structural‐based tunneling (SBT) to provide mutual anonymity for circular P2P structures. In this method, we get help from inherited features of network infrastructure to establish a standard way for making tunnels. SBT introduces a flexible design that is able to manage different parts of the tunnels on current infrastructures. For this purpose, we incorporate SBT with Chord to show how such design can be managed for real‐world applications. The results of applied method with simulations show that by managing critical features of SBT, a trade‐off can be made between stronger security and performance of the network. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : We introduce structural‐based tunneling (SBT) to provide mutual anonymity for circular peer‐to‐peer structures. In this method, we get help from inherited features of network infrastructure to establish a standard way for making tunnels. SBT introduces a flexible design that is able to manage different parts of the tunnels on current infrastructures. For this purpose, we incorporate SBT with Chord to show how such a design can be managed for real‐world applications.